Evaluation of the push-out bond strength of root canal obturation materials filled by four different obturation techniques - Saif N; Nawal A Al Sabawi; Maha M Yahya (College of Dentistry/ University of Baghdad, 2014)
Background: The aim of this study was to comparatively evaluate the push out bond strength (PBS) of root canal fillings using four different obturation techniques (single cone (SC), cold lateral compaction (CLC), continuous wave (CW), and carrier based gutta percha (CBG)). Materials and Methods: Forty mandibular premolar decoronated and instrumented with rotary ProTaper to F3 then teeth were divided randomly into 4 groups of 10 teeth for each as follow: group (I) single- cone obturation with matched-taper gutta-percha, group (II) cold lateral compaction technique, group (III) continuous wave of obturation technique, and group( IV) carrier based gutta-percha technique. Zinc oxide eugenol (ZOE) sealer was used as a root canal sealer for the four groups. After obturation of the root canals, all the roots were sectioned horizontally at three levels in the apical, middle, and cervical thirds of each group. PBS test was performed using digital universal testing machine. Mode of failures was evaluated using digital stereomicroscope (40 X). Collected data were analyzed statistically using one way ANOVA and Tukey test. Results: PBS of CW and CBG significantly higher than SC and CLC, but significantly there were no differences between CW and CBG, and between SC and CLC. Conclusion: Under the condition of this study it can be concluded that thermoplasticized techniques obtain superior PBS of the filling materials in comparisons with cold gutta percha obturation techniques.